L’amianto in epoca preindustriale: da meraviglia della natura ad oggetto di approfondimento scientifico / Asbestos in pre-industrial times: from natural wonder to subject of scientific investigation / Introduzione a “Del Lino incombustibile ovvero della pietra amianto” G.G. Ciampini 1696 - Carnevale, F. (La Medicina del Lavoro, 2012)
Summary «Asbestos in pre-industrial times: from natural wonder to subject of scientific investigation». The author proposes a reading of “Concerning incombustible flax or asbestos stone” which was published in 1696 by Giovanni Giustino Ciampini, who was a historian, a man of the church and scientist in Rome. The text, which was originally written in Latin, is an excellent and early description of the need felt by the majority of scientists in Europe at that time for a change in method: that is, to use scientific experiments to explain and control the natural phenomena observed and even perhaps mythologized right from antiquity. In the case of asbestos this was necessary to check the veracity and consistency of a series of recommendations handed down by the earliest authors but also to revive and reinvent the techniques that had largely been lost so as to be able to utilize and develop a substance that it was thought could be of great benefit to society. In the presentation of Ciampini’s text an attempt is made to recall and contextualize the earliest knowledge on asbestos and follow its evolution over a long historical period, up to the first half of the nineteenth century. It can thus be seen how asbestos, once considered “a wonder of nature”, became a raw material widely used in industrial applications. The most significant steps in this phase of transformation were taken thanks to Italian entrepreneurs and technicians and to the presence of asbestos in the Alpine valleys of Italy. Riassunto Viene riproposto per la lettura “Del lino incombustibile ovvero della pietra amianto”, pubblicato nel 1696 da Giovanni Giustino Ciampini, storico, religioso e scienziato romano. Il testo scritto originariamente in latino rappresenta bene e precocemente l’esigenza di svolta che anima nella stessa epoca la maggioranza degli scienziati europei: ricorrere a delle sperimentazioni scientifiche per spiegare, dominare dei fenomeni naturali descritti e magari mitizzati sin dall’antichità. Nel caso dell’amianto si trattava sia di controllare la veridicità, la coerenza di una serie di segnalazioni tramandate dagli autori più antichi ma anche di resuscitare, reinventare delle tecniche sostanzialmente perdute per lavorare e valorizzare un materiale che, si pensava, sarebbe potuto risultare di grande utilità per la società. Nella presentazione al testo di Ciampini ci si preoccupa di richiamare e contestualizzare le conoscenze più antiche sull’amianto e di seguirne l’evoluzione in un lungo periodo storico, sino alla prima metà dell’Ottocento; si osserva così il passaggio dall’amianto da “meraviglia della natura” a materia prima di impiego industriale. Questa fase di trasformazione si svolge, nelle sue iniziative più importanti, grazie ad imprenditori e tecnici italiani e con l’amianto reperito nelle Valli Alpine.